Characteristics of The Mackerel Tuna Bone Flour (Euthynnus affinis) Produced by Pressure Hydrolysis Method - Cahyono, Eko; Tanod, Wendy Alexander; Ansar, Novalina Maya Sari; Sambeka, Yana (PELAGICUS, 2023)
Fish bones are a by-product or waste from fish processing, both on a small and large scale. Many efforts have been made to utilize these bones by converting them into bone meal. The use of the pressure hydrolysis method in the production of fish bone meal can produce high-quality products. This study aimed to determine the quality of the mackerel tuna bone meal using the pressure hydrolysis method. The data obtained were then discussed descriptively and qualitatively. The results showed that the pressure hydrolysis method effectively produced mackerel tuna bone meal. The highest yield of mackerel tuna bone meal was obtained in the TT2 treatment with a heating time of 2 hours. The bone meal produced had moisture content ranging from 6.58% to 8.76%, ash content ranging from 96.86% to 98.82%, and organoleptic values such as odor, texture, and color were acceptable to the panelists. During storage for 3 days at room temperature, there was mold growth of Aspergillus flavus and Aspergillus penicillium in the range of 1.25×102 to 1.45×102 colonies per gram and met the minimum standards set by the Indonesian National Standard (SNI).